DIETARY PRACTICES, CLINICAL MONITORING AND DIABETESMANAGEMENT AMONG ADULTS WITH TYPE 2 DIABETES MELLITUS - PRETTY RANI and R. NEELA RANI (The Journal of Research, PJTSAU, 2026)
Type 2 diabetes mellitus is one of the most prevalent chronic non-communicable diseases and has become a majorpublic health concern. Hyderabad was purposively selected for the study as it has emerged as one of the metropolitan cities witha high incidence of diabetes and its associated complications. The present study was conducted during 2024 with the purpose ofassessing the dietary patterns, lifestyle habits, clinical characteristics, treatment practices, diagnostic monitoring, diabetes-relatedcomplications, and anthropometric status of adults with Type 2 diabetes mellitus. A descriptive research design was adopted forthe study. A total of 90 diabetic patients attending the outpatient departments of different hospitals in Hyderabad were randomlyselected for the study. Data were collected using a structured interview schedule and analysed using descriptive statistics. Thefindings revealed that the majority of the respondents (64.44%) were non-vegetarians, while 91.11 percent consumed junk foods,84.44 percent consumed cold beverages, and 80.00 percent regularly consumed desserts and confectionery. Nearly half of therespondents (45.55%) had been living with diabetes for 3–6 years, and 83.34 percent reported a family history of diabetes. Mostrespondents (91.11%) managed diabetes with diet and oral hypoglycaemic drugs during the initial stages, whereas dependenceon insulin increased with disease duration. Although 88.89 percent of the respondents underwent fasting and non-fasting bloodglucose tests, only 27.77 percent underwent HbA1c testing and 8.88 percent underwent regular foot examinations. Delayedwound healing (46.66%) and cataract or vision problems (45.55%) were the most commonly reported complications. Anthropometricassessment indicated that 44.44 percent of the respondents were overweight and 38.88 percent were obese. The study emphasizesthe need for nutrition education, healthy lifestyle promotion, regular diagnostic monitoring, and effective diabetes self-managementinterventions to reduce complications and improve the quality of life among individuals with Type 2 diabetes mellitus.